2012
DOI: 10.1017/s095442241200011x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of substituting SFA in dairy products with MUFA or PUFA on CVD risk: evidence from human intervention studies

Abstract: With the substantial economic and social burden of CVD, the need to modify diet and lifestyle factors to reduce risk has become increasingly important. Milk and dairy products, being one of the main contributors to SFA intake in the UK, are a potential target for dietary SFA reduction. Supplementation of the dairy cow's diet with a source of MUFA or PUFA may have beneficial effects on consumers' CVD risk by partially replacing milk SFA, thus reducing entry of SFA into the food chain. A total of nine chronic hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 69 publications
(185 reference statements)
2
89
0
5
Order By: Relevance
“…Different views also exist about the effect of dietary MUFA, and the focus of the debate is the size of the positive effect on controlling chronic disease. According to most of recent reviews, a positive role of dietary MUFA should be existing for human beings, but further researches are needed to elucidate the mechanisms of generating the positive effect (Gillingham et al, 2011;Livingstone et al, 2012;Schwingshackl et al, 2011a,b). In the present study, MUFA were found to display a declining trend in muscle with increased dietary lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Different views also exist about the effect of dietary MUFA, and the focus of the debate is the size of the positive effect on controlling chronic disease. According to most of recent reviews, a positive role of dietary MUFA should be existing for human beings, but further researches are needed to elucidate the mechanisms of generating the positive effect (Gillingham et al, 2011;Livingstone et al, 2012;Schwingshackl et al, 2011a,b). In the present study, MUFA were found to display a declining trend in muscle with increased dietary lipid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This has raised the question of whether replacing a proportion of SFA in dairy fat with MUFA and/or PUFA will lead to reduced CVD risk. The very few RCT that have examined this were reviewed by Livingstone et al (87) who concluded that whilst based on cholesterol changes, there were indications of reduced CVD risk from consumption of milk and dairy products with modified fatty acid composition, compared with those of normal milk fat composition, although the evidence available was weak and inadequate. A new RCT (RESET; ClinicalTrials.…”
Section: Dairy Products and Blood Lipidsmentioning
confidence: 99%
“…I Nurses' Health Study var en høy ratio mellom fete og magre meieriprodukter forbundet med økt risiko for koronarsykdom 162 . Noen har også sammenliknet meieriprodukter med en typisk fettsammensetning med fettmodifiserte meieriprodukter og funnet forbedringer i risikofaktorer av fettmodifiserte meieriprodukter 183,284,285 . Selv om fettsyrer er komponentene i meieriprodukter som trolig har størst innflytelse på blodlipidene, finnes det flere andre naeringsstoffer som påvirker effekten.…”
Section: Melkefettunclassified